@7bangtans.update sebagai Ruang Komunikasi Partisipatif: Analisis Interaksi Antarpenggemar BTS di Instagram - Firyal Putri Fadia; Devy Putri Kussanti; Keriyono Keriyono (STIKes Ibnu Sina Ajibarang, 2026)
Communication is increasingly shifting from a one-way process toward participatory communication that involves the active engagement of all parties, a shift clearly reflected in the growing development of fan accounts on social media. This study aims to analyze and describe how participatory communication occurs on the Instagram account @7bangtans.update as a communication medium among Bangtan Sonyeondan (BTS) fans, focusing on forms of interaction, follower contribution, and the account's role in building an interactive and sustainable communication space for its fan community. This study applied a descriptive qualitative approach within a constructivist paradigm to gain an in-depth understanding of participants' experiences. Data were gathered through non-participant observation of uploads and comment sections, semi-structured in-depth interviews with one account administrator and four active followers, tracing of uploaded content, and a review of relevant literature, then examined through the stages of data collection, data simplification, data display, and conclusion drawing. The findings reveal that the communication pattern on the account fulfils four principles of Paulo Freire's participatory communication theory, namely dialogue built through the comment feature, critical consciousness developing naturally through content exposure, communicative-relational equality between the administrator and followers, and social transformation at the cognitive, affective, and behavioral levels, although each principle is achieved to a different degree. These findings confirm that a fan account on social media can develop into a meaningful participatory communication space for its community, while reinforcing the relevance of Freire's theory within contemporary digital communication.